Efektifitas Aplikasi Hai Girls (Hak Reproduksi Perempuan) Terhadap Pengetahuan dan Sikap Remaja Tentang Hak reproduksi Perempuan (Studi Pada Siswa Sekolah Menengah Atas Di kecamatan Pa - Nessi Meilan; Yudhia Fratidhina; Mardeyanti Mardeyanti (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2022)
Incidents of gender inequality are often in society, due to women's failure to understand reproductive rights. From research data obtained from Titisari I, 2013 about adolescent knowledge aged 17-20 years about reproductive rights at SMK 2 Pawyatan Dhaha Kediri, the results of research were obtained, that most adolescents have less knowledge about reproductive rights. Understanding reproductive rights must be informed earlier, from teens in the senior, junior high school or even in early age. The Department for Education (DfE) created an introductory guide that schools can use to educate how to relate, sex education and health education. This guide is combined with the internet with the target of middle and high school students to support health (NHS, 2019). The purpose of this study is to find out the effect of health education using the Hai Girls application on adolescent knowledge and attitudes about women's reproductive rights in the East Jakarta area in 2022. This research method is a Quasi-experimental research with pre-test and posttest design. The subject of the study was a class X student at Budi Warman 2 High School. The total sample of this study was 80 respondents with inclusion and exclusion criteria and sampling using purpossive sampling techniques. In the results of the study, there was an increase in attitude scores and knowledge before and after treatment in the treatment group with the Hai Girls application and control with a booklet. The highest mean difference was in the treatment group, which was 0.33 in the attitude variable and 7.57 in the knowledge variable. In Indonesia, women are accustomed to even